2023
DOI: 10.3390/biom13030558
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat Diet Related Lung Fibrosis-Epigenetic Regulation Matters

Abstract: Pulmonary fibrosis (PF) is an interstitial lung disease characterized by the destruction of the pulmonary parenchyma caused by excessive extracellular matrix deposition. Despite the well-known etiological factors such as senescence, aberrant epithelial cell and fibroblast activation, and chronic inflammation, PF has recently been recognized as a metabolic disease and abnormal lipid signature was observed both in serum and bronchoalveolar lavage fluid (BALF) of PF patients and mice PF model. Clinically, observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 169 publications
0
4
0
Order By: Relevance
“…Moreover, a high-fat diet could promote the resistance of lung fibroblasts to apoptosis by inhibiting the expression of the death receptor Fas (also called CD95), leading to the progression of pulmonary fibrosis. 251 The Fas promoter in fibroblasts from the murine model of pulmonary fibrosis displayed a reduction in histone acetylation and an increase in H3K9me3, which correlated with elevated expression of HDAC2 and HDAC4. 252 A high-fat diet has also been shown to induce H4K16ac accumulation, leading to pro-fibrotic gene overexpression and collagen deposition in lung fibroblasts.…”
Section: Cells Involved In Metabolic Memorymentioning
confidence: 97%
“…Moreover, a high-fat diet could promote the resistance of lung fibroblasts to apoptosis by inhibiting the expression of the death receptor Fas (also called CD95), leading to the progression of pulmonary fibrosis. 251 The Fas promoter in fibroblasts from the murine model of pulmonary fibrosis displayed a reduction in histone acetylation and an increase in H3K9me3, which correlated with elevated expression of HDAC2 and HDAC4. 252 A high-fat diet has also been shown to induce H4K16ac accumulation, leading to pro-fibrotic gene overexpression and collagen deposition in lung fibroblasts.…”
Section: Cells Involved In Metabolic Memorymentioning
confidence: 97%
“…When lactate binds to GPR81, it can inhibit the lipolysis process in adipocytes through G protein-mediated signaling [ 189 , 190 ]. Interestingly, in IPF lungs, elevated lactate levels are accompanied by dysregulation of lipid metabolism, and the accumulation of lipids in the lungs promotes the progression of IPF [ 191 , 192 , 193 ]. This easily leads to the hypothesis that the elevation of lactate in IPF may contribute to the dysregulation of lipid metabolism in the lungs through its binding to GPR81.…”
Section: Lactate Shuttle and Multicellular Crosstalk In Fibrotic Lungsmentioning
confidence: 99%
“…Pulmonary fibrosis (PF) is a chronic and lethal lung disease that is characterized by the excessive deposition of extracellular matrix (ECM), resulting in impaired gas exchange and lung function ( Moss et al, 2022 ; C; Wang and Yang, 2022 ; J; Yang et al, 2033a ). The most prevalent form of PF is idiopathic pulmonary fibrosis, which has a bleak prognosis and a median survival rate of 2.5–3.5 years following diagnosis ( Strongman et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that Tanis able to prevent podocyte injury and renal fibrosis by effectively blocking glucose-induced oxidative stress and hypoxia-induced EMT in podocytes ( Kang et al, 2020 ). In addition, Tan effectively suppressed the activation of JAK2/STAT3, Wnt, and EGFR signaling pathways, as well as lung fibroblast activation (F. Yang J. et al, 2023 ; D; Shao et al, 2022 ). However, the potential mechanism of Tan in the treatment of pulmonary fibrosis remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%